Food sources of dietary potassium in the adult Japanese population: The International Study of Macro-/Micronutrients and Blood Pressure (INTERMAP) - Okuda,N; Okayama,A; Miura,K; Yoshita,K; Miyagawa,N; Saitoh,S; Nakagawa,H; Sakata,K; Chan,Q; Elliott,P; Ueshima,H; Stamler,J (Nutrients, 2020)
A lower-than-recommended potassium intake is a well-established risk factor for increased blood pressure. Although the Japanese diet is associated with higher sodium intake and lower potassium intake, few studies have examined the source foods quantitatively. Studies on dietary patterns in association with potassium intake will be useful to provide dietary advice to increase potassium intake. Twenty-four-hour (hr) dietary recall data and 24-hr urinary potassium excretion data from Japanese participants (574 men and 571 women) in the International Study of Macro/Micronutrients and Blood Pressure (INTERMAP) were used to calculate food sources of potassium and compare food consumption patterns among quartiles of participants categorized according to 24-hr urinary potassium excretion per unit of body weight (UK/BW). The average potassium intake was 2791 mg/day per participant, and the major sources were vegetables and fruits (1262 mg/day), fish (333 mg/day), coffee and tea (206 mg/day), and milk and dairy products (200 mg/day). Participants in the higher UK/BW quartile consumed significantly more vegetables and fruits, fish, and milk and dairy products, and ate less rice and noodles. Conclusion: Advice to increase the intake of vegetables and fruits, fish, and milk may be useful to increase potassium intake in Japan.